Mitigating High-Fat Diet-Induced Testicular Oxidative Stress and Fibrosis with Bromelain - Gültekin, Burcu; Özen Koca, Raviye; Canbaz, Halime Tuba; Savaş, Hasan Basri; Başaran, Mustafa Berk; Solak Görmüş, Z Işık (The European Research Journal, 2026)
Objectives: Obesity induced by a high-fat diet (HFD) is closely associated with impaired male fertility, primarily through oxidative stress, inflammation, and testicular dysfunction. Natural compounds with antioxidant and anti-inflammatory properties have gained increasing attention for their potential therapeutic effects. Bromelain, a proteolytic enzyme complex derived from Ananas comosus, exhibits antioxidant, anti-inflammatory, and antifibrotic activities, suggesting potential protective effects against obesity-related reproductive impairments. Methods: Male Wistar rats were randomly assigned to four groups (n=9 per group). Animals were fed an HFD for 12 weeks to induce obesity, followed by one month of bromelain supplementation. Testicular tissues were histologically assessed using hematoxylin & eosin (H&E) and Masson’s trichrome staining. Serum and testicular samples were analyzed for antioxidant and oxidative stress markers, including paraoxonase-1 (PON1), arylesterase (ARE), total antioxidant status (TAS), total oxidant status (TOS), and oxidative stress index (OSI). Results: The HFD group showed significant testicular alterations, including thickening of the tunica albuginea, perivascular collagen accumulation, germ cell loss, and disrupted seminiferous tubule architecture (P